Effects of fulvic acid addition on laying performance, biochemical indices, and gut microbiota of aged hens - Xiao, Gengsheng; Liu, Shun; Yan, Xia; Yang, Yang; Qi, Qien; Feng, Xin; Gong, Li; Zhang, Huihua (Frontiers in Veterinary Science, 2022)
The purpose of this study was to evaluate the effect of fulvic acid on performance, biochemical indices, and gut microflora of laying hens in the late stage. 252 55-week-old Dawu Golden Phoenix laying hens were randomly divided into two treatments with six replicates per treatment and 21 chickens in each replicate, including control group (CG) and fulvic acid (500 mg/kg) group (FA). The trial period was eight weeks. Compared with the control group, the FA increased egg weight (P = 0.03), shell-breaking strength (P = 0.03), and reduced egg breaking rate (P < 0.01). There were no significant differences in egg production rate, feed-to-egg ratio, egg shape index, eggshell thickness, and Haugh unit between the two groups but FA increased egg production by 1.45%. Moreover, dietary FA decreased the aspartate aminotransferase levels in serum and increased total antioxidant capacity and glutathione peroxidase (P = 0.04, 0.04, and 0.02, respectively). However, the alpha diversity indices (Ace, Chao1, Shannon, Simpson, goods_coverage, and PD_whole trees) were not different between the two groups. Notably, at the phylum level, the abundances of Firmicutes (P < 0.01) were improved and the abundances of Actinobacteriota (P < 0.01) and Proteobacteria (P < 0.01) were decreased by dietary FA. The supplementation with FA could improve the abundances of Megamonas (P < 0.01) and reduce Enterobacter (P < 0.01) at the genus level. In conclusion, the present study showed that supplementation with 500 mg/kg FA could increase growth performance and egg quality by modulating serum biochemical indices and the cecal microflora abundance and composition of laying hens.